Plasmodium vivax ligand-receptor interaction: PvAMA-1 domain I contains the minimal regions for specific interaction with CD71+reticulocytes (2017)
The malarial parasite's invasion is complex, active and coordinated, involving many low and high affinity interactions with receptors on target cell membrane. Proteomics analysis has described around 40 proteins in P. vivax which could be involved in reticulocyte invasion; few have been studied with the aim of elucidating how many of them establish specific interactions with their respective host cells. Given the importance of knowing which of the parasite's protein regions are functionally important for invasion, minimum regions mediating specific interaction between Plasmodium vivax apical membrane antigen 1 (PvAMA-1) and its host cell were here elucidated. The region covering PvAMA-1 domains I and II (PvAMA-DI-II) specifically bound to the CD71(+) red blood cell subpopulation. A 20 residue-long region ((81)EVENAKYRIPAGRCPVFGKG(100)) located in domain I was capable of inhibiting PvAMA-DI-II recombinant protein binding to young reticulocytes (CD71(+) CD45(-)) and rosette formation. This conserved peptide specifically interacted with high affinity with reticulocytes (CD71(+)) through a neuraminidase-and chymotrypsin-treatment sensitive receptor. Such results showed that, despite AMA-1 having universal functions during late Plasmodium invasion stages, PvAMA-1 had reticulocyte-preferring binding regions, suggesting that P. vivax target cell selection is not just restricted to initial interactions but maintained throughout the erythrocyte invasion cycle, having important implications for designing a specific anti-P. vivax vaccine.